Nephritogenicity of glomerular basement membrane: a molecular aspect - Rauf, Syarifuddin (Paediatrica Indonesiana, 2001)
Glomerular basement membrane (GBM) hasÂ multifunctions. One of its functions is havingÂ nephritogenicitywhich means the ability of an antigen originally from GBM in causing glomerulonephritis, either in experimental animal or in humanÂ being. Recent studies on GBM have revealed that its main component is type IV collagen, consists of 6 differentÂ isoforms, Î±1 (IV) to Î± 6 (IV) chains. Genetic studies show that all of the six Î± chains are encoded by genes located in 2, 13, and X chromosomes. Nephritogenic antigen in GBM has been identified as Î±3, Î±4, Î±5 chains. They are molecules of type IV collagen located in globular domain (NC1 domain) at the carboxyl terminus of the type IV collagen of GBM. They are thought to assemble into a Î±3- Î±4- Î±5 (IV) chain helical molecules in human GBM. Other Î± chains, namely Î±1 and Î±2 chain, are not nephritogenic or poorly nephritogenic, while the Î±6 chain is not located in GBM. TheÂ nephritogenicityÂ of GBM has been elucidated as a cause in experimental anti-GMB nephritis, and in Goodpasture and Alport syndromes.